THE PHENOMENON OF SPIRITUAL ALIENATION AMONG YOUTH IN MODERN SOCIETY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article examines the phenomenon of spiritual alienation among youth in contemporary society and analyzes its causes, manifestations, and consequences. The rapid processes of globalization, digitalization, urbanization, and cultural transformation have significantly influenced young people’s value systems, social relationships, and identity formation. The study explores the impact of social media, consumer culture, virtual communication, and changing moral standards on the spiritual development of youth. Particular attention is given to the role of education, family, and cultural institutions in preventing spiritual alienation and strengthening moral values. The findings suggest that while modern society offers unprecedented opportunities for personal development and self-expression, it also creates conditions that may weaken spiritual awareness, cultural identity, and social connectedness among young people.